2007
DOI: 10.1080/14034940600858433
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Public health policies: A Scandinavian model?

Abstract: There is not one Scandinavian model in public health policy but several: a Danish model mainly adhering to liberal ideals, a Norwegian one that could tentatively be labelled social liberal, and a Swedish model adhering to more social democratic ideals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 3 publications
2
36
0
1
Order By: Relevance
“…For example, studies have shown Danish views on health policy to be more liberal than those in Sweden and Finland, stressing the importance of individual responsibility and autonomy, while the two others emphasize social relations, common values and equality a greater extent. This focus on the obligation of society is also true of Norway that was deemed the least liberal when it came to views on private vs public responsibility for health (Vallgårda 2007(Vallgårda , 2011. Thus it is not clear how ideologically homogeneous the Nordic countries are, and specifically how much such similarities set them apart from the rest of the world.…”
Section: Discussionmentioning
confidence: 98%
“…For example, studies have shown Danish views on health policy to be more liberal than those in Sweden and Finland, stressing the importance of individual responsibility and autonomy, while the two others emphasize social relations, common values and equality a greater extent. This focus on the obligation of society is also true of Norway that was deemed the least liberal when it came to views on private vs public responsibility for health (Vallgårda 2007(Vallgårda , 2011. Thus it is not clear how ideologically homogeneous the Nordic countries are, and specifically how much such similarities set them apart from the rest of the world.…”
Section: Discussionmentioning
confidence: 98%
“…While the two Scandinavian countries studied differ substantially in other areas of public health, 9 they are very similar regarding the issues addressed in this paper. I use two cases to discuss the generalisations presented above.…”
mentioning
confidence: 83%
“…However, there are common factors, including economic arguments such as 'health is an investment in the good life' (Det kongelige helsedepartment 2003: 6) and social democratic ideals (Vallgårda 2007). With these commonalities as a foundation, arguably a Scandinavian model of public health initiatives that includes cultural activities could be implemented across the Scandinavian countries.…”
Section: Looking Aheadmentioning
confidence: 99%
“…There is no common Nordic political approach to public health (Ringsberg and Borup 2011), and different models of public health policy are applied (Vallgårda 2007). However, there are common factors, including economic arguments such as 'health is an investment in the good life' (Det kongelige helsedepartment 2003: 6) and social democratic ideals (Vallgårda 2007).…”
Section: Looking Aheadmentioning
confidence: 99%